A contribuição da história dos conceitos à ciência da informação: Dimensões categórico-abstratas e analítico-causais - Rabello, Rodrigo [UNESP] (IBICT, 2010)
The history of concepts, albeit still little explored by information science, can provide important contributions for the study of key concepts that constitute the theoretical-conceptual framework in a scientifi c context. Thus, the history of concepts is presented as a tool for the study of diachronic and synchronic features of the scientific concept in Information Science. For such, it was imperative to understand the intersection of the categorical-abstract and analytical-causal dimensions, both relevant for constituting the very proposition of the history of concepts elaborated by Reinhart Koselleck.

A história dos conceitos, embora ainda pouco explorada pela ciência da informação, pode fornecer importantes contribuições para o estudo de conceitos-chave que constituem o quadro teórico-conceitual num contexto científico. Nessa direção, a história dos conceitos é apresentada como uma ferramenta para o estudo da diacronia e da sincronia do conceito científico na ciência da informação. Para tanto, foi mister compreender a intersecção das dimensões categórico-abstratas e analítico-causais, ambas relevantes por serem constitutivas da própria proposição da história dos conceitos elaborada por Reinhart Koselleck.
The contribution of the history of concepts to information science: Categorical-abstract and analytical-causal dimensions
Keywords: Epistemology; History of concepts; Information Science; Scientific concepts